2006
DOI: 10.1186/1471-2350-7-65
|View full text |Cite
|
Sign up to set email alerts
|

Lack of MEF2A Δ7aa mutation in Irish families with early onset ischaemic heart disease, a family based study

Abstract: Background: Ischaemic heart disease (IHD) is a complex disease due to the combination of environmental and genetic factors. Mutations in the MEF2A gene have recently been reported in patients with IHD. In particular, a 21 base pair deletion (Δ7aa) in the MEF2A gene was identified in a family with an autosomal dominant pattern of inheritance of IHD. We investigated this region of the MEF2A gene using an Irish family-based study, where affected individuals had early-onset IHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 9 publications
5
17
0
Order By: Relevance
“…15 However, this variant was not associated with MI in our much lager sample of patients with nonfamilial MI and displayed no association with MI in the abovementioned Spanish MI population. 14 Our findings are in line with the results obtained by Weng et al 12 and Horan et al 24 Weng and colleagues found no causative MI mutation in 300 CAD cases, and Horan and associates failed to detect the 21-bp deletion described by Wang et al 10 in 1481 individuals with a positive family history for ischemic heart disease. Similarly, we found no disease-causing mutation in our 23 extended MI families, suggesting that MEF2A mutations are responsible for only a relatively small proportion of familial MI cases.…”
Section: Discussionsupporting
confidence: 80%
“…15 However, this variant was not associated with MI in our much lager sample of patients with nonfamilial MI and displayed no association with MI in the abovementioned Spanish MI population. 14 Our findings are in line with the results obtained by Weng et al 12 and Horan et al 24 Weng and colleagues found no causative MI mutation in 300 CAD cases, and Horan and associates failed to detect the 21-bp deletion described by Wang et al 10 in 1481 individuals with a positive family history for ischemic heart disease. Similarly, we found no disease-causing mutation in our 23 extended MI families, suggesting that MEF2A mutations are responsible for only a relatively small proportion of familial MI cases.…”
Section: Discussionsupporting
confidence: 80%
“…However, the association of MEF2A with CAD/MI has been challenged by subsequent investigations, because the originally described mutations in MEF2A were observed in unaffected individuals and did not segregate with the disease. 12, 15 The advent of Figure 4. Effect of 7 missense mutations on MEF2A transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the role of MEF2A in the pathogenesis of cardiovascular diseases still remains uncertain; in fact, several case-control studies have been undertaken, but controversial results were found. [12][13][14][15][16][17] Moreover, a recent study by Lieb et al 18 performed on more than 1700 patients with MI, 2 large control populations, and extended families with apparently Mendelian inheritance of the disease showed no evidence of association between MEF2A and MI.…”
Section: Clinical Perspective See P 172mentioning
confidence: 99%
See 1 more Smart Citation
“…Kajimoto et al (2005) reported that the CAG repeat sequence was not correlated with MI susceptibility in Japanese patients. Horan et al (2006) also found that the CAG repeat sequence was not associated with the susceptibility to early-onset familial CAD in an Irish population. Hsu et al (2010) identified no correlation between the CAG repeat sequence and CAD susceptibility in the Taiwanese population.…”
Section: Discussionmentioning
confidence: 89%